Parameter extraction using the transfer characteristics of vertically stacked Si nanosheet MOSFETs - Ortiz-Conde, Adelmo; Silva, Vanessa C. P. [UNESP]; Veloso, Anabela; Agopian, Paula G. D. [UNESP]; Simoen, Eddy; Martino, Joao A.; García-Sánchez, Francisco J. (Journal of Integrated Circuits and Systems, 2024)
We present a critical assessment and discussion of the presence of parasitic source-and-drain series resistance and normal electric field-dependent mobility degradation in un-doped Si nanosheet MOSFETs. A simple explicit Lambert W function-based closed-form model, continuously valid from sub-threshold to strong conduction, was used to clearly describe the transfer characteristics. The model was applied to experimental vertically stacked GAA undoped Si nanosheet MOSFETs using phenomenon-related model parameter values extracted from measured data through suitable numerical optimization procedures. The conducted analysis reveals and ex-plains how these two effects produce analogous deleterious con-sequences on these devices’ transfer characteristics.
Keywords: Lambert W function; mobility degradation; nanosheet FETs MOSFETs; parasitic series resistance